Instilling a culture of data security throughout the organisation. Issue 6 (June 2018) - Simmonds, Mike
Abstract : It has long been acknowledged that cyber-security is only as robust as its weakest link. While that could be an unpatched switch or a USB drive left in a company car park, one thing is generally consistent: the weakest part of a 21st Century business's cyber-defences is likely to be its staff. While the threat of the bad guys infiltrating a modern organisation's network may be less than first thought, behaviour that can be just as damaging and expensive to businesses is happening all around us. In fact, we may even be guilty of the contributing factors ourselves. There needs to be a shift in attitude. While implementing the right information security systems is important, organisations must also instil the right culture within the business so that employees understand and respect the importance of data security and don't put the organisation at risk, says Mike Simmonds of Axial Systems.